2001
DOI: 10.4049/jimmunol.167.6.3391
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Stibogluconate Is a Potent Inhibitor of Protein Tyrosine Phosphatases and Augments Cytokine Responses in Hemopoietic Cell Lines

Abstract: Using in vitro protein tyrosine phosphatase (PTPase) assays, we found that sodium stibogluconate, a drug used in treatment of leishmaniasis, is a potent inhibitor of PTPases Src homology PTPase1 (SHP-1), SHP-2, and PTP1B but not the dual-specificity phosphatase mitogen-activated protein kinase phosphatase 1. Sodium stibogluconate inhibited 99% of SHP-1 activity at 10 μg/ml, a therapeutic concentration of the drug for leishmaniasis. Similar degrees of inhibition of SHP-2 and PTP1B required 100 μg/ml sodium stib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
168
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(173 citation statements)
references
References 51 publications
3
168
0
2
Order By: Relevance
“…22 A treatment of Raji-CD4-DCIR cells with SSG for 10 minutes before pulsing with NL4-3 leads to a decrease in HIV-1 binding/entry, whereas it has no similar effect in parental Raji-CD4 cells ( Figure 2A). To determine more specifically which PTPase(s) is implicated in the signal transduced by DCIR after HIV-1 binding, we used specific antisense oligonucleotides directed against SHP-1 and SHP-2 DNA.…”
Section: Shp-1 and Shp-2 Are Involved In Dcir Signaling Induced By Hiv-1mentioning
confidence: 99%
“…22 A treatment of Raji-CD4-DCIR cells with SSG for 10 minutes before pulsing with NL4-3 leads to a decrease in HIV-1 binding/entry, whereas it has no similar effect in parental Raji-CD4 cells ( Figure 2A). To determine more specifically which PTPase(s) is implicated in the signal transduced by DCIR after HIV-1 binding, we used specific antisense oligonucleotides directed against SHP-1 and SHP-2 DNA.…”
Section: Shp-1 and Shp-2 Are Involved In Dcir Signaling Induced By Hiv-1mentioning
confidence: 99%
“…Pharmadynamic studies with sodium stibogluconate earlier revealed drug efficacy in the liver 30. The inhibitory effect with recombinant SHP‐1 has been shown earlier 22. Furthermore, both pharmacological approaches did not influence the expression of the PTPs SHP‐1, SHP‐2, PTP1B, TC‐PTP, DEP‐1 and LAR, which all have been implicated as regulators in insulin signalling or insulin resistance earlier.…”
Section: Discussionmentioning
confidence: 91%
“…In these experiments we could detect a small reduction (~ 13%, P = 0.065) in SHP‐1 activity (not shown). This suggests that – contrasting the strong in vivo metabolic effects and impact on recombinant SHP‐1 22 – the lack of a significant detectable SHP‐1 inhibition in tissues and cultured cells is presumably based on either transient inhibitory efficiency of sodium stibogluconate in vivo or on processing specifics of the animal tissues in vitro . Furthermore, our data showing in vivo efficacy are underlined by demonstration of sodium stibogluconate clearly reducing leishmanial skin lesions in a clinical study in patients applying also the same drug concentration (20 mg·kg −1 ·day −1 ) as in our experimental protocol 41.…”
Section: Discussionmentioning
confidence: 99%
“…The T cell clone JKF6, specific for the melanoma differentiation Ag MART-1 [27][28][29][30][31][32][33][34][35] , was derived from tumor-infiltrating lymphocytes, as previously described (14). These T cells were expanded and activated by using 30 ng/ ml mAb OKT-3, irradiated PBMCs from three donors, and 500 IU/ml recombinant human IL-2.…”
Section: Cellsmentioning
confidence: 99%
“…1). Briefly, a specific TCR-like clonotypic mAb that recognizes the MART-1 [27][28][29][30][31][32][33][34][35] peptide, only when in complex with the HLA-A2 molecule, was used (16,17). JY cells were pulsed with different peptide concentrations, ranging from 500 mM down to 100 pM.…”
Section: Ag Quantitationmentioning
confidence: 99%